Perbandingan Penerapan Akad Rahn di Pegadaian Syariah dan Bank Syariah: Perspektif Kepatuhan Syariah dan Kepuasan Nasabah - Anisa Aulia Fitri; Ulil Albab; Mawardi Mawardi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze and compare the implementation of the rahn contract at Pegadaian Syariah and Bank Syariah from the perspectives of sharia compliance and customer satisfaction. Using a qualitative approach with in-depth interviews with 15 informants, consisting of institution management, sharia supervisors, and customers, the study found that Pegadaian Syariah excels in service aspects, cost transparency, and process convenience, resulting in higher customer satisfaction. On the other hand, Bank Syariah stands out in terms of internal supervision and collateral security, although its administrative process is more complex. Both institutions have adhered to sharia principles in accordance with DSN-MUI fatwas, but there are differences in the technical implementation and service strategies. This study highlights the importance of synergy between service efficiency and sharia compliance in managing rahn products, and contributes to the development of more inclusive and sustainable sharia pawn practices in Indonesia. The findings are expected to provide guidance for sharia financial institutions in improving service quality while maintaining sharia principles.